Report on INFODIDACT 2008 - the First National Conference on Didactics of Informatics: 11-12 April, 2008, Szombathely, Hungary - Juhász, Katalin; Zsakó, László (Teaching Mathematics and Computer Science, 2008)
Acquiring a PhD in any subject has been possible only in the last twentish years in Hungary. To take degree in didactics, especially didactics of informatics is still very difficult. There are not enough forums for the PhD students where they could report of their research work and results.